PERBANDINGAN MODEL PENGARUH MANAJEMEN LABA, GOOD CORPORATE GOVERNANCE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA SUB SEKTOR BATU BARA DAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2020) - Rianto, Dimas Aldi; Gantino, Rilla (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine the effect of Earnings Management, Good Corporate Governance, and Corporate Social Responsibility on the Financial Performance of Companies in Mining Companies in the Coal Sub-sector and Infrastructure in the Telecommunication Sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Earnings Management is measured using Discretionary Accrual. Good Corporate Governance is proxied by IPCG. Corporate Social Responsibility (CSR) is proxied by CSRI. While the company's performance is proxied by Return On Assets (ROA).Sampling by purposive sampling with a total of 20 coal companies and 6 telecommunications companies for the period 2016-2020. This study uses multiple linear regression analysis. Simultaneously Earnings Management, Good Corporate Governance, and Corporate Social Responsibility have a significant effect on Financial Performance in both coal and telecommunications sub-sectors. Good Corporate Governance, Corporate Social Responsibility have a positive and significant effect on financial performance in the coal sub-sector and telecommunications sub-sector. Meanwhile, Earnings Management has no significant positive effect on financial performance in the coal sub-sector. Another finding that earnings management has a negative effect on financial performance and the telecommunications sub-sector and Corporate Social Responsibility has no significant effect.